Assessing EU-Francophone Africa Collaboration: A Systematic Review (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2024)
Over the years, the EU’s soft power has phenomenally grown and spread in the world to the extent that many critics arguably view the Union as a superpower or one of the major global players in today’s world. EU’s global influence is seen in the fact that it is the second largest economy in the world and has continuously represented a very active partner in the development of many sub-regions in the world, including Africa. In effect, the EU has not only been a model for African economies. Through its multiform collaboration with the Black continent, the EU has sought to directly or indirectly affect the lives and growth of specific, if not all African countries. From initiatives aimed at pushing for democracy, peace and economic stability in Africa to infrastructural development and social reforms in Africa, the EU has proved to be a key partner in the socio-political and economic development of Africa. This essay sets out to examine EU policies and programs which in one way or the other have affected the political, economic and socio-cultural sectors of Francophone African countries. The paper specifically looks at the extent to which Francophone African countries’ collaboration with the EU has improved or hindered the progress of African States in terms of political autonomy, economic and technological development and educational and socio-cultural development. The paper is thus divided into three main parts. The first part provides a brief presentation of the EU highlighting its growing influence in the world. The second part critically explores EU presence in Africa and indexes of its impact on the life of African nations. The third part focuses more specifically on the impact of EU-Africa collaboration on Francophone African countries.